Lymphoma of Bone. Issue 1 (January 2018) - Steffner, Robert J.; Jang, Eugene S.; Danford, Nicholas C.
Abstract : Lymphoma can demonstrate primary or secondary involvement of bone. The most common subtype of primary lymphoma of bone is diffuse large B-cell lymphoma. 18-fluorodeoxyglucose positron emission tomography with computed tomography (FDG PET/CT) scanning is important for diagnosis, staging, and assessing the response to therapy. In general, immunochemotherapy should be administered before radiation therapy. The use of radiation for the treatment of lymphoma of bone is controversial. Recent studies have suggested a benefit in terms of local disease control. Orthopaedic surgeons see patients who have skeletal lymphoma at the time of initial workup or in consultation for biopsy and/or the assessment of impending and pathological fractures. Correlating the type and stage of bone lymphoma with prognosis can provide a guide to treatment. The goals for patients with a favorable prognosis include minimizing the need for surgery, limiting surgical morbidity when surgery is needed, and using implants that reduce tumor contamination and thus the field size of radiation if needed.